Pembuatan dan Pemasangan Sistem Penerangan Panel Surya dalam Upaya Peningkatan Aktivitas Peternak Sapi di Desa Lampreh Kecamatan Ingin Jaya Kabupaten Aceh Besar - Tarmizi, Tarmizi; Syahrial, Syahrial; Faturrahman, Faturrahman; Yunida, Yunida (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2024)
Lampreh Village is located in Lamteungoh settlement, Ingin Jaya District, Aceh Besar Regency, this village is one of the assisted villages of Syiah Kuala University. The main potential of this village is agriculture and cattle farming. Activities of cattle farmers such as feeding, cleaning cages, fumigating cows on the Krueng Aceh road in Lampreh Village are only done in the afternoon before the sun gets dark. The problem is that farmers along the Krueng Aceh road do not have lighting and there is no PLN electricity network. In this product-based Community Service, lighting from solar panels (PLTS) has been installed. This PLTS system has a solar panel capacity of 300 WP and a battery of 200 Ah. The total load is 84W, 80% efficiency and can be operated for 22 hours.